2003
DOI: 10.1103/physrevlett.91.136801
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Shot Noise in Resonant Tunneling via Interacting Localized States

Abstract: In a variety of mesoscopic systems shot noise is seen to be suppressed in comparison with its Poisson value. In this work we observe a considerable enhancement of shot noise in the case of resonant tunneling via localized states. We present a model of correlated transport through two localized states which provides both a qualitative and a quantitative description of this effect.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
118
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 24 publications
7
118
1
Order By: Relevance
“…All theoretical work [13][14][15][16] predicted shot noise suppression in the presence of localized states. However, a recent study by Safonov et al 17 also found enhancement of shot noise due to interacting localized states. They investigated the shot noise of a tunnel barrier in an n-GaAs metal-semiconductor fieldeffect transistor ͑MESFET͒.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…All theoretical work [13][14][15][16] predicted shot noise suppression in the presence of localized states. However, a recent study by Safonov et al 17 also found enhancement of shot noise due to interacting localized states. They investigated the shot noise of a tunnel barrier in an n-GaAs metal-semiconductor fieldeffect transistor ͑MESFET͒.…”
mentioning
confidence: 97%
“…A wide variety of noise behaviors due to localized states in mesoscopic systems have been studied both theoretically [13][14][15][16] and experimentally. [17][18][19][20][21] On the other hand, a clear demonstration of the shot noise behavior of an ideal tunnel barrier is still missing for semiconductor systems. In this paper, we report our observation of such a behavior in semiconductor tunnel barriers under various measurement configurations.…”
mentioning
confidence: 99%
See 3 more Smart Citations